Cancer photo-immunotherapy: from bench to bedside - Wang, Miao (Theranostics, 2021)
Targeted therapy and immunotherapy in combination is considered the ideal strategy for treating metastatic cancer, as it can eliminate the primary tumors and induce host immunity to control distant metastases. Phototherapy, a promising targeted therapy, eradicates primary tumors using an appropriate dosage of focal light irradiation, while initiating antitumor immune responses through induced immunogenic tumor cell death. Recently, phototherapy has been employed to improve the efficacy of immunotherapies such as chimeric antigen receptor T-cell therapy and immune checkpoint inhibitors. Phototherapy and immunoadjuvant therapy have been used in combination clinically, wherein the induced immunogenic cell death and enhanced antigen presentation synergy, inducing a systemic antitumor immune response to control residual tumor cells at the treatment site and distant metastases. This review summarizes studies on photo-immunotherapy, the combination of phototherapy and immunotherapy, especially focusing on the development and progress of this unique combination from a benchtop project to a promising clinical therapy for metastatic cancer.